Assessing the development of cognitive control in preterm and full-term infants - Ng, Kai Li (Nanyang Technological University, 2024)
Premature birth has been associated with long-lasting cognitive control difficulties. However, little is known about whether these deficits emerge early in life. Additionally, prior research on perinatal risks to cognitive control has primarily focused on extremely (<28 weeks gestational age) and very preterm (28–32 weeks gestational age) individuals; and neglected the effects of moderate-to-late prematurity (32–37 weeks gestational age). The current paper reports initial results of an ongoing investigation into whether cognitive control differs between preterm and full-term infants, across a wide range of gestational ages, and whether low gestational age is associated with poorer cognitive control. It was hypothesized that preterm infants would demonstrate poorer cognitive control than full-term infants; and that lower gestational age would be associated with greater difficulties. In a preliminary sample of 12- and 18-month-old preterm (N = 15) and full-term infants (N = 15), cognitive control was measured using a response inhibition task, sequential touching task, and a parent-reported scale of effortful control. Linear mixed effects and correlational analyses demonstrated that (1) preterm and full-term infants did not differ in cognitive control and (2) lower gestational age was not associated with poorer cognitive control. Due to the constraints of limited sample size and low statistical power, these non-significant results are not definitive and should be interpreted with caution. The initial findings may inform future research, and several potential areas of exploration are discussed. The present study also underscores the need for further research using larger samples, and adequately powered studies.